A formação do professor no curso de pedagogia em leitura e produção de textos - Santana, Jeter Gomes Gonçalves (2017)
This paper, which is part of the research line "Reading and writing", aims to evaluate the reading and writing difficulties presented by Pedagogy students from a private institution located in the state of São Paulo. We focus on their formation aspects, to verify how a text reading and writing practice, implemented in the course, is being built. For this, we have made a historical recovery of pedagogy and its educational practices, presenting a study about the teachers' graduation. The methodological procedures adopted were: analysis of the Curriculum Guidelines of the Pedagogy Course and application of a questionnaire for a class composed by 65 students from the .3rd semester. The questions were about the students' socioeconomic profile and how these two skills have been worked on graduation. According to students' responses, the concern with reading and writing teaching, most of them say that the training time for the subject is short and for that reason, they don't feel secure to teach these skills on the end of their graduation